Angiotensin-(1-7) improves cognitive function and reduces inflammation in mice following mild traumatic brain injury - Bruhns, Ryan P.; Sulaiman, Maha Ibrahim; Gaub, Michael; Bae, Esther H.; Davidson Knapp, Rachel B.; Larson, Anna R.; Smith, Angela; Coleman, Deziree L.; Staatz, William D.; Sandweiss, Alexander J.; Joseph, Bellal; Hay, Meredith; et al. (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Traumatic brain injury (mTBI) is a leading cause of disability in the US. Angiotensin 1-7, an endogenous peptide, acts at MAS receptors to inhibit inflammatory mediators and decrease reactive oxygen species within the CNS. Few studies have identified whether Ang-(1-7) decreases cognitive impairment following closed mTBI. Materials and Methods: Twenty-four male mice underwent a closed-skull, controlled cortical impact injury. Two hours after injury, mice were administered either Ang-(1-7) (n=12) or vehicle (n=12), continuing through day-5 post-TBI, and tested for cognitive impairment on days 1-5 and 18. pTau, Tau, GFAP, and serum cytokines were measured at multiple time points. Animals were observed daily for cognition and motor coordination via novel object recognition. Brain sections were stained and evaluated for neuronal injury. Results: Administration of Ang-(1-7) daily for five days post-mTBI significantly increased cognitive function as compared to saline control-treated animals. Cortical hippocampal structures of mice showed less damage in the presence of Ang-(1-7). Ang-(1-7) administration significantly changed the expression of pTau and GFAP in cortical and hippocampal regions as compared to control. Discussion: These are among the first studies to demonstrate that sustained administration of Ang-(1-7) following a closed-skull single impact mTBI significantly improves outcomes, potentially offering a novel therapy to prevent long-term CNS impairment.